Revisiting the Applied Model for the Use of Observation: A review of articles spanning 2011-2018 - Ste-Marie, D. M.; Lelievre, N.; Germain, L. (Research Quarterly for Exercise and Sport, 2020)
Purpose: To provide a review of current articles that have used observation interventions to enhance motor skill acquisition or performance of applied tasks, and to situate the research within the Applied Model for the Use of Observation (AMUO) with the goal of forming a basis for evidence-based guidelines for practitioners. Method: Key words (e.g., observation/modeling) were searched in varied data bases (e.g., Google Scholar/PubMed), along with a citation search of the relevant AMUO article, to generate a pool of articles for possible review. Selection criteria included publication between 2011 and 2018, and that the research focus was on the effects of an observation intervention on the acquisition or performance of an applied motor task. Results: Forty-eight articles were reviewed, with 21 of these targeting the basic question of whether observation is effective, and the remaining pertaining to the What, When, Who, and How features of the AMUO. The effectiveness of observation interventions was not only affirmed, but also extended to a wider scope of populations and settings. Greater insight into the necessary information with respect to the demonstration (what) and whether it should be before, after, or during physical practice (when) was obtained. As well, advantages of combining model types (who) and providing control to the learner (how) were reported. Conclusions: While more clarity was brought to certain features of the AMUO that could be used to provide evidence-based guidelines, more research is needed to fully inform practitioners for the effective use of observation interventions.